Legal Status of Village Regulations in the Unitary State of the Republic of Indonesia - Dodi Jaya Wardana; Sukardi Sukardi; Radian Salman (INNOVATION RESEARCH JOURNAL, 2021)
Village regulations are shown as a basic device for the legitimacy of village government administrators in running the village government, in other words, village regulations are prepared as a reference in implementing government and development in the village. The purpose of this studywas to determine the legal status of village regulations in Indonesian legislation. In addition to knowing democratization in running village government. The research method used is a normative legal research method that examines laws and related literature. The results of the study indicate that that the legal status of village regulations in the statutory system is still recognized and the position of Village Regulations as a village legal product has a very strong juridical footing with the enactment of Law Number 6 of 2014 concerning Villages. Although Village Regulations no longer appear in the hierarchy of laws and regulations after the birth or enactment of Law Number 12 of 2011 concerning the Establishment of Legislations, their existence is strictly regulated and the position of Village Regulations is getting stronger because they have been used as a juridical basis for village regulations. With the issuance of Law Number 6 of 2014 concerning Villages.